Element substitution of a spinel LiMn2O4 cathode. Issue 38 (21st September 2021) - Zhang, Shu; Deng, Wentao; Momen, Roya; Yin, Shouyi; Chen, Jun; Massoudi, Abouzar; Zou, Guoqiang; Hou, Hongshuai; Deng, Weina; Ji, Xiaobo
Abstract : Three influence principles of element substitution involving phase evolution, solid solution strengthening and Li + diffusion kinetics boosting. Abstract : Spinel LiMn2 O4 is a promising cathode material for lithium-ion batteries ascribed to its steady bulk structure and abundant manganese sources. Nevertheless, severe capacity decay due to the Jahn–Teller effect and spontaneous disproportionation reaction seriously hampers its extensive application, especially at high-temperature or high-potential operation circumstances. Attributed to the strengthening of the crystallographic structure and the inhibition of Mn 3+ side reactions, element substitution has become one of the most momentous tactics in the modification of LiMn2 O4 . Here, we comprehensively review the developments on restraining capacity fading and enhancing the performances of LiMn2 O4 through element substitution. Primarily, the capacity fading mechanism of LiMn2 O4 has been thoroughly recapitulated. Subsequently, our summary is proposed based on two categories, which are phase evolution and solid solution strengthening invoked by element substitution, and the latter can be subdivided into structure strengthening and Li + diffusion kinetics boosting. More importantly, we put forward a methodological approach for future element substitution research studies. This report will shed light on the future direction of LiMn2 O4 cathode material optimization.